Hubungan Kepatuhan Penggunaan Obat dengan Keberhasilan Terapi Hipertensi di RSUD Waru Pamekasan pada Tahun 2024 - Putri, Diah Arrizah; Suprapti, Herni (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Background: Adherence is one of the definite requirements for for improving therapeutic effectiveness and the patient’s quality of life. Low adherence to prescribed antihypertensive medications is a major factor in uncontrolled hypertension. The patien’s disobedience to the use of drugs can be caused by boredom in taking hypertension medication, and patients often do not remember the time to take medication. Pameksan is one of the districts in East Java, the prevalence of hyeprtension patients in pamekasan has increased in 2017 around 23,16 %. Therefore, this study was conducted to determine whether there is a relationship between compliance with drug use and the success of hypertension therapy at RSUD Waru Pamekasan. Research Methods: This analytical observational study employed a cross-sectional design involving 32 hypertensive patients treated at Waru Pamekasan Hospital. Respondents were selected using a nonprobability sampling technique. The association between variables was analyzed using the chi-square test. Result of Research and Conclusion: The findings indicate a significant association between medication adherence and the therapeutic success of hypertension management among patients at Waru Pamekasan Hospital in 2024, supported by a p-value < 0.05.